The Implementation of Merdeka learning Curriculum in Shaping Student Character in Islamic Religious Education Subjects - Munzir, Munzir; Widodo, Hendro (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Character of education for students is very important, the implementation of an independent curriculum needs to pay attention to the character of students. The quality of future generations is influenced by the formation of student character. analyzing the character development of Islamic religious education students influenced by the independent curriculum is the goal of this study. Library research is used as a research method. Islamic religious education subjects through Pancasila student profiles, it was found that religious values must accompany character education. Student character education cannot be separated from religious education, for several reasons, including the meaning of piety to Allah SWT & adhering to the principles of the Al-Quran Hadith, and based on Pancasila will improve significantly. student character.